CONCURRENT INFECTION OF MONIEZIA EXPANSA AND HAEMONCHUS CONTORTUS IN GOATS AND ITS THERAPEUTIC MANAGEMENT - G. Manojkumar; S. Yogeshpriya; A. Latchumikanthan; N. Premalatha; R. Velusamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Goats are highly susceptible to endoparasitic infections due to free grazing habits. The present study was reported for concurrent infection ofMoniezia expansa and Haemonchus contortus in two goats from a flock of 40 goats in Orathanadu, Thanjavur. History included anorexia, foetid diarrhoea and jowl edema in goats. On clinical examination, pyrexia, pale conjunctival mucous membrane, pasty diarrhoeic faeces, bottle jaw and abdominal thudding were noticed. Coproscopy revealed Moniezia expansa eggs and strongyle eggs and faecal culture revealed Haemonchus contortus larvae. Uneventful recovery was noticed in goats after treating with praziquantel and fenbendazole for 3 days with supportive therapy.